2014
DOI: 10.1111/1744-7917.12131
|View full text |Cite
|
Sign up to set email alerts
|

Identification and localization of two sensory neuron membrane proteins from Spodoptera litura (Lepidoptera: Noctuidae)

Abstract: Sensory neuron membrane proteins (SNMPs), which are located on the dendritic membrane of olfactory sensory neurons (OSNs), are proposed to be associated with odor reception in insects. Recent studies have demonstrated that SNMP1 is essential for electrophysiological responses of OSNs to the sex pheromone, cis-vaccenyl acetate (cVA) in Drosophila melanogaster. To investigate the function of Lepidoptera SNMPs, we cloned two SNMP genes, SlituSNMP1 and SltiuSNMP2, from Spodoptera litura (Lepidoptera: Noctuidae). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 27 publications
6
36
1
Order By: Relevance
“…This result indicates that SNMP2 cannot functionally substitute SNMP1. This functional difference between SNMP1 and SNMP2 is in line with their different cellular expression; whereas SNMP1 is exclusively found in olfactory neurones, SNMP2 is found in supporting cells (Forstner et al ., ; Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This result indicates that SNMP2 cannot functionally substitute SNMP1. This functional difference between SNMP1 and SNMP2 is in line with their different cellular expression; whereas SNMP1 is exclusively found in olfactory neurones, SNMP2 is found in supporting cells (Forstner et al ., ; Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The visualization of the SNMP1 protein in cell bodies and dendrites of sensory neurones within the long trichoid sensilla of H. virescens , which are responsive to pheromone components (Almaas & Mustaparta, ; Baker et al ., ), confirms and extends the original findings on SNMP1 localization in male antennae of the moth Antheraea polyphemus (Rogers et al ., , ). In addition, it has been shown that SNMP1 is also expressed in OSNs on the antennae of female moths (Rogers et al ., , ; Gu et al ., ; Zhang et al ., ) but the identity of these OSNs is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, much progress has been achieved in the identification of SNMP1 and SNMP2 in different insect orders. 103,119,[126][127][128][129][130][131][132][133] ApolSNMP1 mRNA expression increased significantly 1-2 days before adult emergence, coinciding with the functional maturation of the olfactory system. The abundant expression of SNMP1 in pheromonespecific olfactory neurons suggests it may be involved in pheromone detection.…”
Section: Sensory Neuron Membrane Proteinsmentioning
confidence: 90%
“…136,137 This was the first demonstration of SNMP functions in vivo. Additionally, it has been reported that SNMPs display wide expression patterns in different tissues, [129][130][131][132][133] suggesting that they may be involved in some functions beyond olfactory detection.…”
Section: Sensory Neuron Membrane Proteinsmentioning
confidence: 99%